Biaya dan Waktu pada Pelaksanaan Pekerjaan Struktur Balok Precast dan Balok Konvensional - Purnawirati, I.G.A. Neny; Herlambang, Fajar Surya (Universitas Batanghari Jambi, 2024)
Concrete is a construction material that is widely used in Indonesia, when compared to the use of wood and steel materials, there are two methods of concrete work, namely the conventional method and the precast method. In the Kuta Art Market Development Project there are several blocks using the conventional method and some using the precast method. How to compare the cost and time of conventional beam work and the precast method and which method is more effective to use. To be able to determine the choice of the right method to use, an analysis of costs and implementation time is carried out. Furthermore, the results of the analysis are compared so as to get an effective method to use. From the results of the analysis carried out at the Kuta Art Market Development Project, a comparison of costs and implementation time obtained that the total cost for the work of 5 conventional blocks was IDR 47,656,004.04 and the time needed to complete the work of 5 conventional blocks was 5 days. Whereas the total cost required for the work of 5 precast beams is Rp. 46,006,742.42 and the time required to complete the work of 5 precast beams is 4.09 days. When compared, the cost of precast beam work is Rp. 1,649,301.32 (3.5%) cheaper and the execution time for precast beam work is 0.91 days (18%) faster than conventional beam work.